Effects of replacing fish meal with fermented soybean meal on the growth performance, intestinal microbiota, morphology and disease resistance of largemouth bass (Micropterus salmoides) - Hang Yang (Elsevier, 2022)
This study investigated the effects of replacing fish meal (FM) with fermented soybean meal (FSM) on the growth performance, serum biochemical indices, intestinal health, microbial community and disease resistance of largemouth bass (Micropterus salmoides). The basal diet was designed to contain 350 g/kg FM (control, FSM-0), and then, FM was decreased to 300 g/kg, 250 g/kg, 200 g/kg, 150 g/kg by the FSM inclusion of 75 g/kg (FSM-7.5), 150 g/kg (FSM-15.0), 225 g/kg (FSM-22.5) and 300 g/kg (FSM-30), respectively. The five diets were fed to largemouth bass with initial body weight of 21.2 ± 0.1 g for 8 weeks. The results showed that FSM-30 group presented lower weight gain, and FSM-22.5 and FSM-30 groups displayed higher feed conversion ratio than those of the control group (P < 0.05). No significant difference was observed in whole body composition (moisture, crude protein, crude lipid and crude ash) among all the groups (P > 0.05). Compared with the control, the protein retention in FSM-30 group, the lipid retention in FSM-15, FSM-22.5 and FSM-30 groups, and serum superoxide dismutase activity and total antioxidant capacity in FSM-22.5 and FSM-30 groups were decreased (P < 0.05). Moreover, the foregut villus height was reduced in all the FM-replaced groups, but the villus height, muscle thickness and villus circumferences of foregut were promoted in FSM-15, FSM-22.5 and FSM-30 groups. In terms of intestinal microorganism, FSM-22.5 and FSM-30 groups had lower abundance of Cetobacterium and higher abundance of Mycoplasma than those of the control group (P < 0.05). In the challenge test with intraperitoneal injection of Aeromonas hydrophila, the cumulative mortality was lowered in FSM-22.5 group (P < 0.05). In conclusion, in a basal diet containing 350 g/kg FM, FSM could be included at 150 g/kg to replace 100 g/kg FM without negative effects on the growth, feed utilization and intestinal health of largemouth bass.